Kirk-Othmer Encyclopedia of Chemical Technology 2011
DOI: 10.1002/0471238961.trankenn.a01
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Fate of Agrochemicals in the Environment

Abstract: Synthetic agrochemicals applied at high concentration in the environment for pest control inevitably disperse from these sites, affecting non‐target species. As expected from the second law of thermodynamics, they will dilute spontaneously, transported into the available sinks in the environment by all transport mechanisms available. These dispersing chemicals comprise a diversity of manufactured products considered essential for modern economic civilisation, largely based on the consumption of fossil fuels. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…These data indicated that on an industry scale, the used of herbicides following the introduction for Roundup Ready had not changed significantly on average for all forms of cotton, largely because of greater use on conventional cotton (Crossan et al 2007;Kennedy et al 2011). These results were surprising, but consistent with the previous predictions regarding the selection of particular herbicides.…”
Section: Roundup Ready Cottonsupporting
confidence: 81%
See 4 more Smart Citations
“…These data indicated that on an industry scale, the used of herbicides following the introduction for Roundup Ready had not changed significantly on average for all forms of cotton, largely because of greater use on conventional cotton (Crossan et al 2007;Kennedy et al 2011). These results were surprising, but consistent with the previous predictions regarding the selection of particular herbicides.…”
Section: Roundup Ready Cottonsupporting
confidence: 81%
“…Monitoring of trash ginned from cotton during the 2002 season occurred over a 2-year period at three gin sites from different valleys (Crossan and Kennedy 2008 pesticide residues were detected in gin trash; 13 commonly used pesticides of cotton and DDE, the main aerobic breakdown product of DDT (Kennedy et al 2011). The concentrations of these residues were then characterised for risk of contaminating water using standard methodology (ECOFRAM 1992;Norton et al 1992) and the EPA guidelines (EPA 1999).…”
Section: Regarding Concerns Of Cgt Contaminating Waterways and Naturamentioning
confidence: 99%
See 3 more Smart Citations